Landscape metrics applied to formerly reclaimed saltmarshes: a tool to evaluate ecosystem services? - Almeida, Diana (2016)
Analyses of saltmarsh ecosystem services have been particularly focused on the capacity of mitigating climate change effects to cope with rising sea levels and concerning flood management. Nevertheless, ecosystem stability is vital for accurate service delivery, but land-use changes and coastal erosion are affecting saltmarshes. This provides the background for one of the primary arguments for protecting saltmarshes. Landscape metrics were selected according to shape, complexity, and connectivity parameters, and added to average elevation and distance to the coast, for two years - 1972 and 2010. We developed an equation that measures coastal protection, taking into account the results of PCA and the percentage of explained variation of each component (coastal defence index: ES_CoastDef). Three saltmarshes located in the Algarve region, Portugal, were selected to apply the coastal defence index. Individual patches were analysed according to saltmarsh typologies. Results revealed that every saltmarsh decreased its coastal defence from 1972 to 2010; changes in shape and connectivity metrics affect mostly the index performance. In 1972, natural saltmarshes offered a better coastal defence than the other typologies, but in 2010 formerly reclaimed saltmarshes comprised higher values of coastal defence. Positive evolutions in terms of reclaimed saltmarshes have enabled them to provide coastal defence ecosystem services. Thus, through this index it is possible to outline target coastal defence parameters and design strategies for their conservation and consider ecological restoration.